2011
DOI: 10.1590/s1806-66902011000200001
|View full text |Cite
|
Sign up to set email alerts
|

Calagem e adubação boratada na produção de feijoeiro

Abstract: Resumo -Objetivou-se avaliar os efeitos da aplicação de calcário e boro nos atributos químicos de um Latossolo, estado nutricional e produtividade da cultura do feijoeiro. As doses de calcário empregadas foram crescentes, considerando-se a saturação por bases igual a 70%, correspondendo às doses: zero; 0,6; 1,2 (v = 70%); 1,8 e 2,4 t ha -1. O calcário utilizado apresentava poder relativo de neutralização total (PRNT), poder de neutralização (PN) e reatividade (RE) de 131; 137 e 95%, respectivamente. As doses d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
5
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 8 publications
7
5
1
8
Order By: Relevance
“…However, the increase obtained in the number of grains per pod a result of borated fertilization up to the 1.31 kg ha -1 B rate was not reflected in bean productivity growth. This result is inconsistent with other studies (Mascarenhas et al, 1998;Mariano et al, 1999;Souza et al, 2011), which found a positive response by bean plants to borated fertilization, certainly due to the supply of the plant nutritional needs for boron directly from the soil.…”
Section: Agronomic Aspects Of Cropscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the increase obtained in the number of grains per pod a result of borated fertilization up to the 1.31 kg ha -1 B rate was not reflected in bean productivity growth. This result is inconsistent with other studies (Mascarenhas et al, 1998;Mariano et al, 1999;Souza et al, 2011), which found a positive response by bean plants to borated fertilization, certainly due to the supply of the plant nutritional needs for boron directly from the soil.…”
Section: Agronomic Aspects Of Cropscontrasting
confidence: 99%
“…The boron content in common and castor leaves in the two cropping systems was affected by the treatments, especially with the higher levels tested, which confirms other research results that found increased boron leaf contents in response to the application of increasing levels of borated fertilizers to common bean (Mariano et al, 1999;Souza et al, 2011) and castor (Lange et al, 2005). However, no boron deficiency/toxicity symptoms were found in either culture, under the two systems investigated, in response to the treatment application.…”
Section: Nutritional Aspects Of Cropssupporting
confidence: 87%
“…Therefore, it was expected that the application of B in the foliar tissue, being a fertilization closer to the reproductive stage could influence positively the grain yield, however, it was inferior to the application in the soil. Similar results were obtained by Souza et al (2011), working with 0, 0.6, 1.2, 1.8 and 2.4 kg ha -1 of B in common bean crop that obtained maximum grain yield at the dose of 1.8 kg ha -1 of B. Muhmood et al (2014), researching borated fertilization on wheat, obtained higher grain yield at the dose of 2 kg ha -1 and Debnath et al (2011), which found a higher yield of wheat grain at a dose of 1.9 kg ha -1 B.…”
Section: Technisupporting
confidence: 90%
“…Cakmak et al (1995) comprovaram que, por causa de o B garantir a integridade da membrana plasmática, houve efluxo 45 vezes maior de K em folhas de girassol, deficientes em B, em relação às folhas bem nutridas. Segundo Dechen & Nachtigall (2006), o B interfere na absorção e no metabolismo dos cátions, assim como observado por Souza et al (2011), com aumento no teor de Mg na parte aérea do feijão, em função do aumento da dose de B.…”
Section: Resultsunclassified